Preliminary study on social network among Malay SMEs entrepreneurs : gender differences / Oswald Timothy and Ehsan Fansuree Surin - Timothy, Oswald; Surin, Ehsan Fansuree (2012)
We take stock of the current body of knowledge and understanding on social network theory and structuralist perspectives to further argue that the effects of structural characteristics on social network differ between men and women. Specifically, we investigate social network, defined as interrelationship between the entrepreneurs and their contact (alter) in business venturing (Fombrun, 1982), among Malay SMEs in Malaysia. The use of social network is considered an important factor for the development of the firm (Birley, 1995). However, there is limited understanding on how the entrepreneurs use their social network (Heald-Fisher, 2010). Moreover, there is dearth attention given to investigate the social network in Malaysia. Both social network theory and structuralist perspective were employed in this quantitative- based study. The data gathered through the mail questionnaire method in which 105 are men and 81 are female respondents represent 53% responded. Using t-test, the study reveals that there is no significant difference in terms of size of network, network activity and network density for both genders. Finally, this study discuses managerial implications and highlights future research directions.